Pulmonary Vein Stenosis: Moving From Past Pessimism to Future Optimism - McLennan, Daniel I.; Solano, Elyan C. Ruiz; Handler, Stephanie S.; Lincoln, Joy; Mitchell, Michael E.; Kirkpatrick, Edward C. (Frontiers in Pediatrics, 2021)
Pulmonary Vein Stenosis (PVS) is a rare disease with a prevalence of around 1.7 cases per 100000 children under 2 years old. Treatment options for this disease have not provided great results and pathophysiology of this condition is still poorly understood. Here, we will review the history of PVS including diagnostic tools and treatments, the current management approach, and what the future holds for this devastating disease